(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
Using the example of the Italian film industry of the 1960s and 1970s and, in particular, popular erotic thriller cycles, the article focuses on different types of time periods closely associated with film production: the shooting stage and the phase of apprenticeship for newcomers. These labour temporalities were fraught with hierarchical tensions and power imbalances. Directors appropriated the length of film shooting as a means of occupational distinction. Under the pretext of apprenticeship, experienced mentors took advantage of moneyless trainees who lacked a personal network of supportive film practitioners. Apprentices weathered through this period in anticipation of fairly compensated freelance work.